Population Viability of Rorippa columbiae : Multiple Models and Spatial Trend Data - Elizabeth E. Crone; Janet L. Gehring (Conservation Biology, 1998)
In managing rare species for conservation, we often need to make decisions based on existing, scanty data sets. Our ability to use such data effectively may be critical to our success in managing individual populations. We used viability analysis to examine the population dynamics of a threatened plant species, Rorippa columbiae , on Pierce Island in Washington (U.S.A.). Although the island was protected in part because of the presence of R. columbiae , monitoring suggested that plant density declined on the island after the preserve was established. To understand the implications of this decline, we generated a number of hypotheses about factors that might be important in controlling population dynamics in R. columbiae : density dependence, size dependence, spatial environmental heterogeneity among sites, and dispersal and colonization of new sites. Using statistical and biological criteria, we were able to rule out the hypotheses of size‐dependent population growth rates and dispersal among sites, but the importance of spatial heterogeneity and density dependence was ambiguous. Models with and without spatial heterogeneity make radically different predictions about the future of R. columbiae on Pierce Island: with spatial heterogeneity we expect persistence, albeit at a limited number of sites, whereas in a spatially uniform environment we expect extinction in the near future. This emphasizes the uncertain future of this population but tells us that ecological differences among sites and correlates of population vigor are important data to collect in future studies. Our analysis also points to the importance of maintaining multiple working hypotheses about controls of population growth when interpreting population trends from limited data. Viabilidad Poblacional de Rorippa columbiae : Modelos Múltiples y Datos de Tendencia Espacial Al manejar especies escasas de cara a su conservación, a menudo se necesitan tomar decisiones basadas en una información existente, que con frecuencia es escasa. La habilidad en el uso de estos datos de manera efectiva, puede determinar de forma crítica nuestro éxito en el manejo de poblaciones. En este estudio, se utilizan análisis de viabilidad para examinar la dinámica poblacional de una especie vegetal amenazada, Rorippa columbiae , en la isla Pierce, Washington. Aunque uno de los motivos para proteger la isla fue la presencia de R. columbiae, el seguimento realizado sugiere que su densidad dismiuyó tras la protección de este espacio. Para entender las implicaciones de dicha disminución, se generaron una serie de hipótesis sobre los factores que pueden ser importantes para controlar la dinámica poblacional de R. columbiae : dependencia de la densidad, dependencia del tamaño, heterogeneidad espacial entre localidades y dispersión/colonización. Mediante el uso de criterios estadísticos y biológicos, nos fue posible descartar las hipótesis de crecimiento poblacional dependiente del tamaño y de dispersión entre áreas. Sin embargo, la importancia de la heterogeneidad espacial y de la dependencia de la densidad es ambigua. Incluir o no la heterogeneidad espacial en los modelos, da como resultado predicciones radicalmente distintas sobre el futuro de R. columbiae en la isla de Pierce: al incluir la heterogeneidad espacial se predice persistencia, aunque en un número limitado de localidades, mientras que en un medio espacialmente uniforme, se predice la extinción en un futuro próximo. Esto aumenta nuestra incertidumbre sobre el futuro de la población, pero destaca que las diferencias ecológicas entre localidades y las correlaciones de salud poblacional son datos importantes para recolectar en estudios futuros. Nuestro análisis también apunta la relavancia de manejar múltiples hipótesis de trabajo para predecir las dinámicas poblacionales a la hora de interpretar las tendencias poblacionales basadas en datos limitados.